Analysis of consumer behavior of organic dragon fruit At Naura Farm, agrotourism, Jember district - Arifin, Tomy; Widjayanti , Fefi Nurdiana; Prayuginingsih, Henik (International Applied Science, 2023)
An agricultural subsector that has potential and is able to develop rapidly in Indonesia is the horticultural subsector, one of the horticultural subsectors is organic dragon fruit. This research aims to: (1) describe the characteristics of consumer behavior towards organic dragon fruit at Naura Farm Jember; (2) analyze the level of consumer satisfaction of organic dragon fruit at Naura Farm Jember . This research was carried out by CV. Naura Farm Agrotourism. This location selection was done randomly intentionally ( purposively ). Type method study Which chosen is descriptive analytical. The sampling method uses total sampling, namely all visitors to Naura Farm on Saturdays and Sundays. Determination size sample calculated with a total of 33 respondents. Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The research results show that: (1) Consumers of organic dragon fruit are male (61.61%) and age range 18–24 years (30.30%), domiciled in Jember (100%), University or Student (36 .36%), the last level of education they had was Senior High School (SMA) (30.30%); (2) The consumer satisfaction index as measured by the Customer Satisfaction Index (CSI) is 75.42%, meaning that the majority of consumers are satisfied with the overall performance of organic dragon fruit .